2015
DOI: 10.1080/08957959.2014.999057
|View full text |Cite
|
Sign up to set email alerts
|

High pressure inactivation ofClostridium botulinumtype E endospores in model emulsion systems

Abstract: Clostridium botulinum type E is a cold-tolerant, neurotoxigenic, endospore-forming organism, primarily associated with aquatic environments. High pressure thermal (HPT) processing presents a promising tool to enhance food safety and stability. The effect of fat on HPT inactivation of C. botulinum type E spores was investigated using an emulsion model system. The distribution of spores in oil-in-water (O/W) emulsions and their HPT (300-750 MPa, 45-75°C, 10 min) inactivation was determined as a function of emuls… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…To date, few studies investigated the HPT inactivation of spores from the important food intoxicating organism, C . botulinum , in food matrices and food model systems [ 7 10 , 14 ]. Moreover, the comparison of inactivation data is not only difficult due to varying process parameters but also because of different thermodynamic properties of HPT units, in particular controlling and monitoring adiabatic heating effects.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…To date, few studies investigated the HPT inactivation of spores from the important food intoxicating organism, C . botulinum , in food matrices and food model systems [ 7 10 , 14 ]. Moreover, the comparison of inactivation data is not only difficult due to varying process parameters but also because of different thermodynamic properties of HPT units, in particular controlling and monitoring adiabatic heating effects.…”
Section: Discussionmentioning
confidence: 99%
“…For spores of non-proteolytic C . botulinum type E, it has been shown that increasing fat content can result in reduced HPT and thermal inactivation [ 14 , 15 ]. Both GPH and SS have a higher fat content than BV (braised veal) and VS (vegetable soup), namely 12.8% and 8.6%, respectively.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation